Trichoderma asperellum suppresses viral diseases and promotes the growth and yield of country bean - Ali Hossain, Muhammed; Tanjum Swarna, Fariha; Al Arabi, Rabeya; Hamim, Islam (Frontiers in Agronomy, 2023)
Virus-caused diseases are the main adversaries of country bean (Lablab purpureus Lin.) production in Bangladesh. Potyviruses and cucumber mosaic virus (CMV) were found in country bean leaves that displayed virus-like symptoms. This study looked at the growth and yield of country bean plants that had been treated with Trichoderma asperellum to control country bean viruses. T. asperellum-treated plants exhibited decreased disease incidence and severity, as well as a drop in vector population, when compared to control plants. Plant growth was enhanced in soil drenched with T. asperellum suspension, with an increase in the number of leaves per plant, pods per plant, root length, weight of dried pods/plant, and weight of dried seeds/plant. Finally, our findings suggest that T. asperellum could be an effective treatment for controlling viral diseases of country bean in Bangladesh.